Effect of Treatment With Tabalumab, a B Cell–Activating Factor Inhibitor, on Highly Sensitized Patients With End‐Stage Renal Disease Awaiting Transplantation. Issue 4 (18th January 2016) - Mujtaba, M. A.; Komocsar, W. J.; Nantz, E.; Samaniego, M. D.; Henson, S. L.; Hague, J. A.; Lobashevsky, A. L.; Higgins, N. G.; Czader, M.; Book, B. K.; Anderson, M. D.; Pescovitz, M. D.; et al.
Abstract : B cell–activation factor (BAFF) is critical for B cell maturation. Inhibition of BAFF represents an appealing target for desensitization of sensitized end‐stage renal disease (ESRD) patients. We conducted a Phase 2a, single‐arm, open‐label exploratory study investigating the effect of tabalumab (BAFF inhibitor) in patients with ESRD and calculated panel reactive antibodies (cPRAs) >50%. The treatment period duration was 24 weeks. Eighteen patients received tabalumab, at doses of 240‐mg subcutaneous (SC) at Week 0 followed by 120‐mg SC monthly for 5 additional months. Patients were followed for an additional 52 weeks. Immunopharmacologic effects were characterized through analysis of blood for HLA antibodies, BAFF concentrations, immunoglobulins, T and B cell subsets, as well as pre‐ and posttreatment tonsil and bone marrow biopsies. Significant reductions in cPRAs were observed at Weeks 16 (p = 0.043) and 36 (p = 0.004); however, absolute reductions were small (<5%). Expected pharmacologic changes in B cell subsets and immunoglobulin reductions were observed. Two tabalumab‐related serious adverse events occurred (pneumonia, worsening of peripheral neuropathy), while the most common other adverse events were injection‐site pain and hypotension. Three patients received matched deceased donor transplants during follow‐up. Treatment with a BAFF inhibitor resulted in statistically significant, but not clinically meaningful reduction in the cPRA from baseline (NCT01200290, Clinicaltrials.gov). Abstract : Treatment with a B cell–activating factor inhibitor in highly sensitized end‐stage kidney disease patients awaiting kidney transplant produces pharmacodynamic effects but does not lead to clinically meaningful reduction in calculated panel reactive antibodies.